2019
DOI: 10.1155/2019/4935615
|View full text |Cite
|
Sign up to set email alerts
|

Radiographically Occult Carcinomatous Spread of Breast Cancer to the Liver: A Challenging Case

Abstract: Metastatic carcinomatosis to the liver is a pattern of malignant infiltration that tends to provoke hepatic fibrosis. It is a rare complication of multiple solid tumor types and often seen in the absence of discrete tumor mass in the liver. We report a case of a 69-year-old woman with metastatic ductal carcinoma of the breast who presented with rising serum tumor markers and mildly cirrhotic contour of the liver on a CT scan. An early diagnosis of occult spread to the liver was made by means of a percutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…At present, diagnosis of PLC is mostly achieved by imaging examination, and multislice spiral computed tomography (MSCT) can clearly display the liver conditions, which is of high clinical application value [ 4 , 5 ]. It was found that the detection rate of contrast-enhanced CT scans was about 80.0%, but its diagnostic efficiency might be compromised in the detection of small tumors, which requires additional diagnostic means to enhance the diagnostic accuracy [ 6 , 7 ]. Tumor markers such as alpha-fetoprotein (AFP), tumor-specific growth factor (TSGF), and Golgi protein 73 (GP73) are commonly used for tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…At present, diagnosis of PLC is mostly achieved by imaging examination, and multislice spiral computed tomography (MSCT) can clearly display the liver conditions, which is of high clinical application value [ 4 , 5 ]. It was found that the detection rate of contrast-enhanced CT scans was about 80.0%, but its diagnostic efficiency might be compromised in the detection of small tumors, which requires additional diagnostic means to enhance the diagnostic accuracy [ 6 , 7 ]. Tumor markers such as alpha-fetoprotein (AFP), tumor-specific growth factor (TSGF), and Golgi protein 73 (GP73) are commonly used for tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…BCLM was diagnosed using iodine contrast-enhanced abdominal CT or gadoxetic acid (Primovist)-enhanced liver MRI. BCLM was classified into five categories based on the number and configuration of the metastatic lesions: oligometastases (≤3 metastatic hepatic lesions with clear margins), nonconfluent metastases (≥4 nonconfluent metastatic hepatic lesions), confluent metastasis (hepatic metastasis with confluent nodules), infiltrative liver metastases (diffuse infiltrative metastases involving bilateral hepatic lobes), and pseudocirrhosis (development of a diffuse nodular contour of the liver with widespread hepatic metastases) [ 20 , 21 , 22 , 23 ]. An experienced senior radiologist interpreted and classified patients’ radiologic scans in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…Malignancy is the etiology of ascites in approximately 10% of cases [1,2]. Ascites in the setting of primary extrahepatic solid tumors may occur due to peritoneal seeding, portal hypertension from massive liver metastasis, obstruction of lymphatics, treatment complications, or infiltration of hepatic sinusoids with malignant cells [3,4]. Peritoneal carcinomatosis appears to cause ascites by producing proteinaceous fluid from tumor cells lining the peritoneum, and extracellular fluid enters the peritoneal cavity to restore the oncotic equilibrium and was reported to account for 53% of malignancy-related ascites in one series [5].…”
Section: Introductionmentioning
confidence: 99%